Determinants of Symptoms of Diabetic Peripheral Neuropathy: Findings from a Community-based Study from Rural Haryana, India - Aishwarya Sharma; Sudhir Shekhawat; FNU Shalini; Shivanshu Kaushik; Sunil Arora (International Journal of Advanced Medical and Health Research)
Introduction: Diabetes mellitus is a chronic disorder involving the metabolic system of blood glucose. Its progression involves the micro and macro circulation of the body, affecting the heart, kidneys, retina, peripheral vessels, and nerves. Developing countries like India have a high burden of diabetic peripheral neuropathy (DPN). The aim of this study was to screen for DPN using a validated tool, the Michigan Neuropathy Screening Instrument (MNSI), and identify the determinants of DPN symptoms. Methodology: A total of 175 diabetics with a duration of illness of more than 5 years, attending the outpatient services of the community health center, Jhajjar, were screened from March to April 2023. Fasting blood sugar values were noted. We collected history, performed an examination, and applied MNSI to screen for DPN. Results: The prevalence of DPN symptoms was 37.7% and 60.6%, respectively, according to the MNSI history and MNSI physical assessment sections. The major determinants of DPN symptoms were literacy (odds ratios [OR] = 31.1, 95% confidence Intervals [CI] = 3.5–275.4, P = 0.002) and fasting blood glucose (OR = 11.1, CI = 3.7–33.0, P < 0.001). Conclusion: Enhancing health education with regard to glycemic control and screening for complications can potentially help in reducing the morbidity associated with diabetes.